STRATEGI OPTIMALISASI PUBLIKASI LAYANAN MAPS (MOBIL ANTAR PULANG SEHAT) MELALUI PROMOSI TERPADU DI MEDIA SOSIAL DAN MEDIA CETAK PADA RSUD JENDERAL AHMAD YANI METRO - Aprilianingsih, Maya; PERTIWI, WINDI; Irfan, Muhammad Fuadul (Journal of Hospital Administration and Excellent Health Service, 2025)
ABSTRACTIntroduction: RSUD Jenderal Ahmad Yani Metro launched an innovative public health service called MAPS (Mobil Antar Pulang Sehat), a free transport service for post-inpatient patients residing in Metro City. Despite its benefits, the service remains underutilized due to limited public awareness. Method: This descriptive study used observational methods and in-depth interviews with hospital staff. The USG method was employed to prioritize problems, and fishbone analysis was used to identify root causes. Result: The primary issue identified was lack of promotion. Interventions included integrated promotion strategies via social media platforms (Instagram, Facebook) and printed media (banners, posters, pamphlets). Conclusion: Integrated promotion significantly improved awareness and utilization of the MAPS service, highlighting the importance of structured communication in public health service delivery.